PENGELOLAAN KEUANGAN HASIL PETERNAKAN DAN PERTANIAN WARGA BERBASIS NILAI EKONOMI HINDU DI DUSUN ALAS MALANG - Nila Cahya, Ni Nengah; I Nyoman Suarna; Ni Nengah Sudarsini; Sri Sofiana amni; I Komang Purnama Yasa (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The Community Service Program (KKN) conducted in Dusun Alas Malang, Tempos Village, Gerung District, West Lombok Regency, aims to improve financial management of agricultural and livestock income among the local residents through an educational participatory approach. In this program, students provide education on the importance of simple and systematic financial record-keeping and its positive impact on household economic resilience. Ten residents engaged in agricultural and livestock activities were the primary target group for this program. Through observations and interviews, it was found that most residents were not accustomed to recording income and expenses from their businesses, leading to traditional financial management that was undocumented and ineffective. The program was carried out in four phases: data collection and socialization, education, mentoring, and evaluation. In the data collection phase, the community was educated about the importance of financial record-keeping using a simple cash book format. During the education phase, materials on financial management and Hindu economic values were presented to provide a spiritual perspective on managing wealth. The mentoring phase aimed to guide residents in applying daily financial record-keeping. The evaluation showed that 85% of participants felt more knowledgeable about good financial management and were ready to continue maintaining records independently. This program successfully raised awareness among the community about the importance of wise, sustainable financial management that aligns with Hindu economic values.